The Art Collection of Sears Bank and Trust Company. (Chicago : Sears Bank and Trust Company, 1980)
Booth, Cameron ; christo ; Dine, Jim ; Ferrari, Virginio ; Francis, Sam ; Ginzel, Roland ; Hunt, Richard ; Ito, Miyoko ; Janssen, Horst ; Jenkins, Paul ; Johns, Jasper ; Lenor Larsen, Jack ; Lichtenstein, Roy ; Martyl ; Motherwell, Robert ; Nickle, Robert ; Oldenburg, Claes ; Rauschenberg, Robert ; Rivers, Larry ; Rosenquist, James ; Slepak, Paul ; Stella, Frank ; Warhol, Andy ; Wesselmann, Tom ; Yoors, Jan
The Art Collection of Sears Bank and Trust Company, Sears Bank and Trust Company, Chicago, October 15 through November 21, 1980
boek